A comparative study between chemically modified and copper nanoparticle immobilized Nylon 6 films to explore their efficiency in fighting against two types of pathogenic bacteria. (5th January 2020) - Swar, Sumita; Máková, Veronika; Horáková, Jana; Kejzlar, Pavel; Parma, Petr; Stibor, Ivan
Graphical abstract: Highlights: Efficient functionalization of Nylon 6 was achieved by grafting mPEG. The antibacterial efficacy was improved by copper nanoparticle incorporation. The antibacterial activity against pathogenic bacteria was performed among all samples. The cytocompatibility for copper nanoparticle deposited samples was accomplished. Abstract: Hospital-acquired infections (HAI) caused by pathogenic bacteria such as Pseudomonas aeruginosa and Staphylococcus aureus adversely affect public health due to their colonization and subsequent formation of a biofilm on medical devices. Various functionalized polymers including polyamides are commonly used in the biomedical industry aiming to resist bacterial infection as well as to ensure cytocompatibility of the used materials. The present study is focused on the extension of our previous work that developed a new approach to immobilize mPEG on an amine-activated Nylon 6 surface. Herein, we compare functionalized samples of Nylon 6 together with samples additionally containing copper nanoparticles (Cu NPs, size 40–60 nm) physisorbed on a modified surface. Modified samples were analyzed via different techniques including water contact angle measurements, atomic force microscopy and scanning electron microscopy associated with energy dispersive X-ray spectroscopy. The copper functionalized samples showed high antibacterial efficacy against Gram-positive Staphylococcus aureus and Gram-negative Pseudomonas aeruginosa . Moreover, most of the prepared samples were cytocompatible.